2021
DOI: 10.1007/s00432-021-03519-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of regulation of DNA methyltransferase isoforms in human breast tumors

Abstract: Significant reprogramming of epigenome is widely described during pathogenesis of breast cancer. Transformation of normal cell to hyperplastic cell and to neoplastic phenotype is associated with aberrant DNA (de)methylation, which, through promoter and enhancer methylation changes, activates oncogenes and silence tumor suppressor genes in variety of tumors including breast. DNA methylation, one of the major epigenetic mechanisms is catalyzed by evolutionarily conserved isoforms namely, DNMT1, DNMT3A and DNMT3B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 327 publications
(349 reference statements)
0
21
0
1
Order By: Relevance
“…The earlier reports have shown that the aberrant DNA methylation activity of DNMT3B is linked to the development and progression of breast cancer ( 35 , 57 ). Nonetheless, the mechanisms of DNMT3B-mediated DNA hypermethylation remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier reports have shown that the aberrant DNA methylation activity of DNMT3B is linked to the development and progression of breast cancer ( 35 , 57 ). Nonetheless, the mechanisms of DNMT3B-mediated DNA hypermethylation remain obscure.…”
Section: Discussionmentioning
confidence: 99%
“…DNMTs are a family of enzymes that catalyze the reaction of addition of the methyl group to cytosine residues within CpG dinucleotides using S-adenosylmethionine as a methyl donor. A recent analysis of regulation of DNA methyltransferase isoforms in human breast tumors revealed that DNMT1, DNMT3A, and DNMT3B promoters harbor multiple ERα-binding sites [154].…”
Section: Epigenetics As Unifying Mechanismmentioning
confidence: 99%
“…breast tumors revealed that DNMT1, DNMT3A, and DNMT3B promoters harbor multiple ERα-binding sites [154]. A sex bias in DNA methylation levels, usually associated with sex-biased gene expression, was found in many animal and human studies [155][156][157].…”
Section: Epigenetics As Unifying Mechanismmentioning
confidence: 99%
“…DNA methylation is well-studied epigenetic modification that plays a key role in the regulation of gene expression ( 1 ). In mammals, DNA methylation primarily occurs within CpGs and is catalytically executed by a family of enzymes called DNA methyltransferases, DNMTs, which are classified as either maintenance or de novo methyltransferases ( 2 ) Maintenance methyltransferase DNMT1, maintains DNA methylation pattern during replication throughout the life of an organism, whereas de novo methyltransferases DNMT3a and DNMT3b establish methylation pattern during gametogenesis. With S-adenosylmethionine (SAM) acting as a methyl donor, DNMTs catalyze the addition of a methyl group to the fifth carbon of the cytosine residue ring of a CpG dinucleotide, generating 5-methylcytosine ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA methylation function of DNMT1 is reported to be modulated by post-translational modifications, which include phosphorylation, ubiquitination, methylation and acetylation ( 2 ). Mass spectrometry analyses indicate that human DNMT1 activity is regulated at the post-translational level through phosphorylation at the N-terminal domain ( 2 ), and phosphorylation by kinases Akt and PKC at this domain resulted in disruption of DNMT1 interaction with its partners and promoted global hypomethylation ( 11 ). Phosphorylation of DNMT1 at the C-terminal domain influenced the abundance and activity of DNMT1 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%